Morphology of testate amoeba Difflugia australis (Playfair, 1918) Gautier-Lièvre et Thomas, 1958 from a subtropical reservoir (southeast China) - Ndayishimiye, Jean Claude; Nyirabuhoro, Pascaline; Wang, Wenping; Mazei, Yuri; Yang, Jun (Zootaxa, 2020)
Difflugia australis, first described by Playfair (1918), has a unique morphotype. However, in the absence of morphometric data, it has not yet been reliably classified within the largest testate amoeba genus Difflugia. In this study D. australis collected from a subtropical reservoir in southeast China was investigated by means of light and scanning electron microscopy. Basing on biometrical data, we provide an improved diagnosis of this little known species. Difflugia australis is different from other similar congeners (i.e., D. bacillariarum Perty, 1849 and D. elegans Penard, 1890) mainly by the combination of the following features: the shell is broadly ovate, with rounded dome and convex sides converging down to a very short distance from the aperture and diverging suddenly into a short rim (collar). It is usually more or less asymmetrical, with one side being more dilated than the other. The shell surface is slightly smooth, composed of flat siliceous plates of irregular shape and size, mixed with fine grains; microbial spores of comparable forms are spread on the shell surface; particles are often interspersed with a network of organic cement with unique mesh pattern; one (sometimes two) slanting spine-like posterior end of the shell is variable in form; collar is mainly formed by small plates of equal size. The dimensions of the shell are: total shell length 88–106 µm; shell width 53–88 µm; aperture diameter 19–28 µm; collar height 3–6 µm; spine length 3‒23 μm. The size frequency distributions of both total shell length and shell width indicate that it is a size-monomorphic species with low variability.